Design And Development Of An Insect-Inspired Micro Air Vehicle - Cheaw, Boon Hong (Universiti Sains Malaysia, 2019)
Micro Air Vehicles (MAVs) are now an active research focus that has caught attention from global talents. With its’ small size, MAVs have considerable potential to be capable of performing missions such as environmental monitoring, surveillance and assessment in hostile situation. Through the process of mimicking insect flight, however, researchers from both in educational institution and industry are facing a lot of challenges such as instability of the air vehicle during the hovering, the maneuverability, the propulsive efficiency due to miniaturization. The objective is to innovate an efficient four-winged FW-MAV platform with better payload carrying capability, where human can allocate important payloads on the FW-MAV during environmental monitoring and indoor surveillance missions. Using Computer Aided Design (CAD) software SolidWorks, the FW-MAVs’ wing and tail are designed. With the allocated time and financial support, two wings are developed using traditional cut and glue method and advanced vacuum mold method. Avionics connection is tested before assembling with the wing and tail. Flight test and vertical thrust measurement are conducted on FW-MAV to compare the performance of different wings and different model at full throttle maximum speed. In general, the FW-MAV produces maximum vertical thrust at 10° angle of attack. Wing which has the stiffeners and manufactured using vacuum mold produces the highest thrust compare with other wings. Possible future work is to optimize the tail design and control algorithm in order to achieve hovering flight.